Quality Deterioration of Boiled Salted Carp Fish (Cyprinus carprio), Processed using Different Cooking Methods, During Chilling Storage - Dwi Suryaningrum, Theresia; Syamdidi, Syamdidi (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Study on quality changes of boiled salted Carp fish, processed using different cooking methods during chilling storage has been conducted. The study was intended to obtain an information on the effect of cooking method on the shelf-life of boiled salted carp fish (Cyprinus carpio) at chilling temperatures. Fish was soaked in a 0.2% of alum solution and then marinated in condiment solution for 30 minutes. Fish were cooked for 4 h by two different methods i.e steaming and boiling, at 98-100 oC, and then dried in the oven at 80-90 oC for 1 hour. Boiled salted fish then were stored at chilling room (2-4 oC) and observed every 3 days for 15 days. The quality of boiled salted fish were analyzed i.e proximate at the beginning and the end of storage, while moisture content, pH, TVB, total plate count, mold and sensory test were conducted during chilling storage. The results showed that steamed boiled salted carp fish had higher protein content, pH and also have better product which was preferable by the panelists. Based on this result steaming method was recomended to be used as processing method for production of boiled salted carp fish from fresh water. Sensory test found that panelists preferred steamed product which had a good appearance, odor, taste and texture. However steamed product had faster increase of moisture content, TVB, and number of bacteria as well as the decrease of pH value and odor causing faster deterioration of product compared to boiling method. Based on microbiological tests, the boiled salted carp fish cooked by steaming methods were safe to be consumed before 6 days and the boiling method before 9 days, since storage exceed that periods resulted in number of bacteria already reached the maximum number allowed and became not suitable for human consumption.